Dust Scattering Albedo at Millimeter Wavelengths in the TW Hya Disk - Tomohiro C. Yoshida; Hideko Nomura; Takashi Tsukagoshi; Kiyoaki Doi; Kenji Furuya; Akimasa Kataoka (The Astrophysical Journal)
Planetary bodies are formed by coagulation of solid dust grains in protoplanetary disks. Therefore, it is crucial to constrain the physical and chemical properties of the dust grains. In this study, we measure the dust albedo at millimeter wavelength, which depends on dust properties at the disk midplane. Since the albedo and dust temperature are generally degenerate in observed thermal dust emission, it is challenging to determine them simultaneously. We propose to break this degeneracy by using multiple optically thin molecular lines as a dust–albedo-independent thermometer. In practice, we employ pressure-broadened CO line wings that provide an exceptionally high signal-to-noise ratio as an optically thin line. We model the CO J = 2–1 and 3–2 spectra observed by the Atacama Large Millimeter/submillimeter Array at the inner region ( r < 6 au) of the TW Hya disk and successfully derive the midplane temperature. Combining multiband continuum observations, we constrain the albedo spectrum at 0.9–3 mm for the first time without assuming a dust opacity model. The albedo at these wavelengths is high, ~0.5–0.8, and broadly consistent with the L. Ricci et al., DIANA, and DSHARP dust models. Even without assuming dust composition, we estimate the maximum grain size to be ~340 μ m, the power-law index of the grain size distribution to be >−4.1, and the porosity to be <0.96. The derived dust size may suggest efficient fragmentation with a threshold velocity of ~0.08 m s ^−1 . We also note that the absolute flux uncertainty of ~10% (1 σ ) is measured and used in the analysis, which is approximately twice the usually assumed value.